Lessons From Astronomy and Biology for the Mind—Copernican Revolution in Neuroscience - Northoff, Georg (Frontiers in Human Neuroscience, 2019)
Neuroscience provides major insights into the neural correlates of mental features like consciousness and sense of self. Despite these major advancements, we do not know the mechanisms connecting neuronal and mental states, the neuro-mental mechanisms that allow transforming neuronal activity into mental states. We propose that neuroscience may benefit from the kind of Copernican turn that, initiated by Copernicus and Darwin, revolutionized the fields of physics and biology. Specifically, I claim that we need to abandon our currently rather anthropocentric ‘vantage point from within brain’ by a more allo-centric ‘vantage point from beyond brain’. I first show how Copernicus and Darwin, due to the shift of their vantage point from within to beyond earth and humans, were able to take into view the non-specialness of earth and humans, e.g., what is shared between earth and other planets as well as between human and non-human species. Such specialness is still presupposed in current neuroscience which regards the neural correlates of mental features like consciousness that are supposed to be special when compared to those of non-mental features. That is possible only by presupposing a pre-Copernican ‘vantage point from within brain’. Recent data as illustrated in this paper, show a neuronal continuum between conscious and unconscious states; that defies the supposed specialness of the neuronal mechanisms underlying mental features. Mental features like consciousness may then signify rather a specific degree on a broader neuronal continuum that ranges from non-consciousness over unconsciousness and consciousness to extended consciousness. The neuronal mechanisms underlying mental features can then be characterized by non-specialness (rather than specialness) which presupposes a ‘vantage point from beyond brain’. Such vantage point from beyond brain, in turn, allows taking into view the shared features between neuronal and mental features, i.e., their “common currency”. That same “common currency” may, in turn, allow addressing and searching for those mechanisms that allow transforming neuronal activity into mental states, e.g., neuro-mental transformation. In conclusion, I propose that neuroscience may benefit in its search for the neural basis of mind from a Copernican turn analogous to the one initiated by Copernicus and Darwin in physics and biology.